Multiple capsid-stabilizing interactions revealed in a high-resolution structure of an emerging picornavirus causing neonatal sepsis - Shabih Shakeel (Nature Portfolio, 2016)
Human parechovirus 3 (HPeV3) can cause severe central nervous system infections and is a major cause of neonatal sepsis. Here the authors determine the structure of HPeV3 that provides a high-resolution view of the capsid’s organization and shows multiple interactions of the RNA genome with coat proteins.